2022
DOI: 10.1111/imm.13613
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the efficacy of anti‐immunoglobulin E monoclonal antibodies in the treatment of allergic asthma

Abstract: The present study aims to evaluate the efficacy of an anti‐immunoglobulin E monoclonal antibody (omalizumab) in the treatment of allergic asthma (AS). A total of 34 patients with moderate‐to‐severe bronchial asthma admitted to the Respiratory Department of Tianjin First Central Hospital between September 2019 and September 2021 were enrolled in this study. The patients were treated with omalizumab in addition to conventional inhaled corticosteroids + long‐acting β2 agonist treatment. The therapeutic effects be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The study results showed that regardless of whether treatment lasted for a full four months or not, omalizumab therapy signi cantly reduced hospitalization days, lowered total hospitalization costs, and out-of-pocket expenses, while also signi cantly improving patients' asthmarelated subjective symptom scores. These ndings are consistent with results from other domestic and international studies [13,14].…”
Section: Discussionsupporting
confidence: 93%
“…The study results showed that regardless of whether treatment lasted for a full four months or not, omalizumab therapy signi cantly reduced hospitalization days, lowered total hospitalization costs, and out-of-pocket expenses, while also signi cantly improving patients' asthmarelated subjective symptom scores. These ndings are consistent with results from other domestic and international studies [13,14].…”
Section: Discussionsupporting
confidence: 93%
“…By binding to free circulating IgE and downregulating IgE receptors on mast cells, basophils, and dendritic cells, it can reduce disease progression in allergic asthma. 157 Omalizumab is mainly used for severe refractory allergic asthma with elevated serum IgE levels (<1300 IU/mL) as classified in the fifth level of the Global Initiative for Asthma guidelines, and it can be administered to children over 6 years old. As a precision treatment, it has good safety and tolerability and can improve symptom control and quality of life in patients with severe refractory allergic asthma.…”
Section: Treatmentmentioning
confidence: 99%